Exploring Female Hadith Transmitters: A Gender Perspective as a Modern Women’s History Lesson through Intelligent Ṣaḥabiyyāt - Friyadi, Arif; Masruri, Muhammad; Abdillah, Aufa; Fatah, Abdul; Sadili, Imam (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2024)
Islam encourages women to achieve the highest intellectual and spiritual abilities and does not prioritize men over women. The early generation of Islam, known as the Ṣaḥabiyyah (companions of the Prophet), played a significant role in narrating hadith from the first to the next generation. This study explores the role of the Ṣaḥabiyyāt (female companions of the Prophet) in narrating the greatest source of Islam, especially the hadith. The study uses a qualitative method, collecting data and inventorying female narrators from Jawāmi’ul Kālim software. The results show that over 160 female narrators from the time of the the Ṣaḥabat or Tābi’in played an active role in the transmission of hadith to the next generation. The intelligence of the Ṣaḥabiyyat not only became teachers but also of prominent male companions. The study can motivate females to be at the forefront of education and scientific transformation without fear of gender differentiation.